The Influence of Work Culture, Human Resource Management Practices, Communication, and Compensation on the Performance of Private Vocational High School Employees - Nani Sudiarti; Tri Widyaastuti; I Nyoman Sawitri; Zahara Tussoleha Rony (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
The Influence of Work Culture, Human Resource Management Practices, Communication, and Compensation on the Performance of Private Vocational High School Employees